Skimmia anquetilia N.P. Taylor and Airy Shaw (Rutaceae): A Critical Appriasal of its Ethnobotanical and Pharmacological Activities - Nabi, Masarat; Tabassum, Nahida; Ganai, Bashir Ahmad (Frontiers in Plant Science, 2022)
Skimmia anquetilia N.P. Taylor and Airy Shaw (Rutaceae) is a perennial, aromatic, gregarious wild ornamental shrub native to the Western Himalaya. The plant is used in the traditional medicinal system to treat copious health conditions like rheumatism, fever, inflammation, headache, influenza, body-ache, clearing of the nose, diabetes, lowering the body temperature, smallpox, wounds, burns, snake, and scorpion bites. Phytochemical and gas chromatography-mass spectrometer (GC-MS) analysis of S. anquetilia showed the presence of alkanes, alkenes, carboxylic acids, fatty acids, and their esters, simple coumarins, terpenes, phenylpropanoid, and so on. These active principles exhibit a wide array of pharmacological effects, including anti-inflammatory, antioxidant, anti-cancerous, anti-feedant, and antibacterial properties. Most pharmacological studies were based on the essential oil and the crude extracts of the plant and the bioactive compounds responsible for the bioefficacy have not been well-identified. Further investigations are required to transform the experience-based claims on the use of S. anquetilia in traditional medicine practices into evidence-based information. Detailed in-vitro and in-vivo studies on the mechanisms of action of pure bioactive compounds and more elaborate toxicity studies to ensure plant safety for human use should be conducted. This review recapitulates the current status of its use in the ethnobotany, phytochemistry, and pharmacological activities. It also offers a critical assessment of the plant’s existing information which would help to recuperate its potential as a source for drug development of lead molecules.